Sosialisasi Peningkatan Nilai Tambah Produk Hortikultura Over Supply di Desa Sembalun Timba Gading - Suliartini, Ni Wayan Sri; Rizki, Rama; Alhadawiah, Sabila; Arafah, Putri Nurul (Universitas Mataram, 2025)
Sembalun Timba Gading is a village located at the foot of Mount Rinjani. This village has an agroclimate that is suitable for cultivating horticultural crops and is a center for vegetable and fruit production in East Lombok. Abundant production during the harvest season causes prices to drop drastically, while these products spoil quickly so they cannot be stored for long. This results in losses for farmers. Therefore, processing of agricultural products is needed, especially horticulture, which can increase the shelf life and selling value of the product. On the other hand, the lack of knowledge and skills of farmers causes horticultural products to be sold as fresh products. Farmers' knowledge and skills about processing horticultural products need to be improved through socialization and training. The initial step in increasing knowledge is needed through socialization activities. The Mataram University community service team carried out community service in the form of socialization of increasing the added value of oversupply horticultural products in Sembalun Timba Gading Village. The target partners are the Ndak Kuta Farmer Group and the Kali Empit Farmer Group which are engaged in the cultivation of horticultural and plantation crops. The method used in this socialization activity is counseling with material presentation by resource persons and continued with a discussion session. The socialization activity went smoothly. Participants were very enthusiastic about participating in the activity because they considered the material provided to be very useful for improving the quality of agricultural products and increasing the selling value of products. The understanding of target partners about horticultural product processing increased as evidenced by the active participants asking questions and the results of group discussion assignments which resulted in four types of product processing that were decided to be pursued, namely making mashed potato chips, making chili flour, making chili sauce, and making shallot oleoresin.